Arsenic content in commercial fish of the Barents Sea (according to long-term data) - M. A. Novikov; E. A. Gorbacheva; A. M. Lapteva (Известия ТИНРО, 2021)
Total content of arsenic in muscles and liver of the main commercial fish species landed in the Barents Sea, as atlantic cod Gadus morhua, haddock Melanogrammus aeglefinus, long rough dab (american plaice) Hippoglossoides platessoides, greenland halibut Reinhardtius hipoglossoides, and european plaice Pleuronectes platessa is considered on the data collected in 2009–2020. The average As content in the muscles of examined fish met hygienic standards for the permissible concentration, i.e. 5 μg/g of wet weight, but the content in liver was about twice higher. High variability of the total As content in muscles of juveniles and adult fish was observed that imposed excessive restrictions on their sales as food products. Taking into account that the increased content of arsenic in tissues of fish in the Barents Sea has natural origin, these restrictions are not directly related to actual quality of the fish raw materials. There is recommended to account the natural background of As and establish a regional criterion for the allowable concentration of total arsenic in the muscles of fish landed in the Barents Sea as 12 μg/g WW. For principal decision on the safe level of arsenic content in fish products, introduction of a new standard for the level of inorganic arsenic content is recommended, that is more reliable and representative indicator.